Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1034/j.1601-0825.8.s2.5.x
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal diseases and HIV infection

Abstract: The workshop considered six related questions about periodontal changes seen in HIV infection. 1) To what extent are specific periodontal changes associated with HIV? 2) Are conventional periodontal diseases modified by HIV infection? The changes associated with HIV appear to be modified presentations of conventional diseases. Research should identify initiation and progression factors for necrotizing diseases. 3) What is the role of geography and transmission groups? These questions cannot be answered without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 52 publications
0
22
0
Order By: Relevance
“…Severe periodontal diseases have been associated with the alterations in the host immune system, which can predispose to gingivitis and the development of periodontitis. Moreover, the relevance of the immune system in the protection of the periodontal tissues has been documented and the impairment of this system could aggravate the periodontal status [28] Previous studies have shown that the microbiology of gingivitis and periodontitis in the HIV patients may differ significantly in comparison to these periodontal pathologies in immunecompetent individuals [29,30].…”
Section: Resultsmentioning
confidence: 99%
“…Severe periodontal diseases have been associated with the alterations in the host immune system, which can predispose to gingivitis and the development of periodontitis. Moreover, the relevance of the immune system in the protection of the periodontal tissues has been documented and the impairment of this system could aggravate the periodontal status [28] Previous studies have shown that the microbiology of gingivitis and periodontitis in the HIV patients may differ significantly in comparison to these periodontal pathologies in immunecompetent individuals [29,30].…”
Section: Resultsmentioning
confidence: 99%
“…The presence of the anaerobic bacteria, enterobacteria and superinfecting microorganisms may be relevant in the gingivitis and periodontitis etiology, especially in immunodeficent patients (1,14,16). However, the role of the enteric bacteria plays in the periodontal diseases etiology remains unclear, and it must be an alert to clinicians who use systemic antibiotics, such as ciprofloxacin as an adjunct in the periodontitis treatment in such patients (18).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that microbiology of gingivitis and periodontitis in HIV patients may differ significantly in comparison to these periodontal pathologies in immunecompetent individuals (1,16). These peculiarities are not related to the distribution of the strictly anaerobic (14), but probably it can involve superinfecting microorganisms and other pathogenic agents normally not involved in periodontal infections, such as fungi and enteric organisms (1,17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with NUP and necrotizing stomatitis frequently complain of extreme pain and spontaneous bleeding. 21 Severe deep-aching jaw pain can be one of the hallmarks. "Punched-out" dental papilla, soft tissue and bone necrosis, spontaneous bleeding, deep seated pain, mouth odour, reddish in appearance, spontaneous exfoliation of teeth, necrosis of the bone, and swelling are common.…”
Section: Necrotizing Ulcerative Periodontitis (Nup) ( Figure 13)mentioning
confidence: 99%